Country Economic Memorandum for Sao Tome and Principe - Background Note 10 : What are the Obstacles to Agricultural Development in STP? A Review of Current Agriculture Production Structure and Potential - Arias, Diego; Horton, John; Valdivia, Pablo (World Bank, Washington, DC, 2019)
This note presents an analysis of the obstacles and opportunities for STP’s agriculture value chains, assesses the main sector risks, and provides a series of public sector recommendations for increased private sector investment. While the country will remain a net importer of food and agricultural products for the foreseeable future, a series of opportunities exist, some to increase import-substitution, others to expand exports. Given STP’s land constraints and climate variability, importing food will continue to occur in the near to medium-term future to satisfy local demand. However, import-substitution opportunities will continue to offer prospects centered on the feedstuff-livestock chain and the horticultural sector, as well as some additional expansion of the palm oil industry. Export opportunities lie primarily in cocoa products as well as in emerging non-traditional agricultural exports, some strategically linked to tourism, especially eco-tourism already embraced by the government and by high end tourist developments established in the past few years. Analysis of the competitiveness of existing and emerging rural supply chains in STP reveals a series of characteristics that allow to overcome the structural diseconomies of scale of a small island state. These characteristics include among others: (i) high value-to-weight products, (ii) agricultural products that can be taken with tourists, (iii) low perishability and products that can be stored, (iv) climate change resilience; and (v) explore the country’s uniqueness. Value chains that possess some of these key characteristics discerned from the analysis offer private sector opportunities, provided the enabling environment allows them to reach their potential.